2023
DOI: 10.20517/jeea.2022.22
|View full text |Cite
|
Sign up to set email alerts
|

Ethylbenzene exposure in North America - an update

Abstract: Chronic ethylbenzene exposures and attendant potential health risks for United States children and prospective parents were first evaluated under the United States Environmental Protection Agency’s Voluntary Children’s Chemical Evaluation Program. Using updated data and methods, a 2015 reevaluation observed declines in ethylbenzene releases and concentrations in ambient and indoor air. Both assessments identified inhalation as the dominant exposure route and smoking as the greatest contributor, with dietary in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…In contrast, the central tendency for styrene exposure levels was 0.1 ppm (434 µg/m 3 ), with 1 ppm (4343 µg/m 3 ) as the upper bound. These data indicate a high degree of conservatism in using styrene exposure levels in ethylbenzene/styrene production workers as an approximation of ethylbenzene exposure, and even greater conservatism when those data are used to estimate ethylbenzene exposure among the general population (Kester and Morgott 2023 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast, the central tendency for styrene exposure levels was 0.1 ppm (434 µg/m 3 ), with 1 ppm (4343 µg/m 3 ) as the upper bound. These data indicate a high degree of conservatism in using styrene exposure levels in ethylbenzene/styrene production workers as an approximation of ethylbenzene exposure, and even greater conservatism when those data are used to estimate ethylbenzene exposure among the general population (Kester and Morgott 2023 ).…”
Section: Discussionmentioning
confidence: 97%
“…Until and unless future work on ethylbenzene carcinogenesis convincingly falsifies that conclusion, research on the toxicity of ethylbenzene that is applicable for human risk assessment should be focused on ethylbenzene exposures that approximate foreseeable human exposure levels, which are more than three orders of magnitude below the KMD identified here. The most recent, comprehensive evaluation of ethylbenzene exposure (Kester and Morgott 2023 ) showed that in styrene production facilities, personal exposure concentrations to ethylbenzene collected over the 20-year period 2000 to 2020 were typically below the limit of detection (LoD). In contrast, the central tendency for styrene exposure levels was 0.1 ppm (434 µg/m 3 ), with 1 ppm (4343 µg/m 3 ) as the upper bound.…”
Section: Discussionmentioning
confidence: 99%